Reproducibility of resting state spinal cord networks in healthy volunteers at 7 Tesla - Barry, Robert L. (Neuroimage, 2016)
We recently reported our findings of resting state functional connectivity in the human spinal cord: in a cohort of healthy volunteers we observed robust functional connectivity between left and right ventral (motor) horns and between left and right dorsal (sensory) horns (Barry et al., 2014). Building upon these results, we now quantify the within-subject reproducibility of bilateral motor and sensory networks (intraclass correlation coefficient = 0.54–0.56) and explore the impact of including frequencies up to 0.13 Hz. Our results suggest that frequencies above 0.08 Hz may enhance the detectability of these resting state networks, which would be beneficial for practical studies of spinal cord functional connectivity.